Endovascular treatment of postoperative aortic coarctation aneurysms—a single center experience - Dimitrova, Iva N.; Simeonov, Peyo (Frontiers in Cardiovascular Medicine, 2024)
BackgroundFormation of local type aortic aneurysm years after surgical repair of coarctation (CoA) occurs in 10% of patients independent of the surgical technique and is a potentially life-threatening condition if left untreated with a high risk of aortic rupture. Redo open surgery is associated with 14% in-hospital mortality and a high risk of complications. Endovascular treatment appears to be a feasible alternative with a high success rate and low morbidity and mortality, but data concerning long-term results is still mandatory. We describe the single center experience of a series of patients treated with endovascular stent grafting for large aneurysms after previous surgery for CoA.MethodsThis series involves 12 consecutive patients treated with endovascular stent grafting from April 2003 to January 2022 for late aneurysm at the site of previous surgical repair for CoA. Data on baseline characteristics, clinical, computed tomography (CT), procedural features, and in-hospital and long-term results were analyzed. All patients signed institutional informed consent for the procedure.ResultsA total of 12 patients (average age 38.5 ± 10.2 years) underwent endovascular repair. The average interval between the initial surgical intervention and the aneurysm repair was 24.1 ± 9.1 years and the majority (83.3%) underwent synthetic patch aortoplasty as previous intervention. All patients were symptomatic at presentation with an average maximum diameter of the aneurysm 67.2 mm (ranging from 44 to 110 mm). Stent-graft placement was successful in all cases without procedural, in-hospital, 30-day, and one-year mortality or major complications. The average hospital stay was 9.3 days (range 7–19 days). For a mean follow-up period of 87 months (range, 23–168 months), all patients demonstrated positive aneurysm remodeling with cavity thrombosis and aneurysm diameter reduction to 54.9 mm (±16,6). For the entire follow-up period, we observed one aneurysm-related death and three deaths of heart failure.ConclusionEndovascular stent-graft treatment of patients with thoracic aneurysms after repair of CoA is an acceptable treatment of choice. It has shown promising results with high technical success and low immediate, short—and mid-term morbidity and mortality. Still, randomised control trials (RCTs) are needed to define the long-term outcome of this approach. Routine surveillance and screening of patients with previous CoA repair are mandatory.